Assessment of individual organ doses in a realistic human phantom from neutron and gamma stimulated spectroscopy of the breast and liver. Issue 6 (7th May 2014) - Belley, Matthew D.; Segars, William Paul; Kapadia, Anuj J.
Abstract : Purpose: Understanding the radiation dose to a patient is essential when considering the use of an ionizing diagnostic imaging test for clinical diagnosis and screening. Using Monte Carlo simulations, the authors estimated the three‐dimensional organ‐dose distribution from neutron and gamma irradiation of the male liver, female liver, and female breasts for neutron‐ and gamma‐stimulated spectroscopic imaging. Methods: Monte Carlo simulations were developed using the Geant4 GATE application and a voxelized XCAT human phantom. A male and a female whole body XCAT phantom was voxelized into 256 × 256 × 600 voxels (3.125 × 3.125 × 3.125 mm 3 ). A monoenergetic rectangular beam of 5.0 MeV neutrons or 7.0 MeV photons was made incident on a 2 cm thick slice of the phantom. The beam was rotated at eight different angles around the phantom ranging from 0° to 180°. Absorbed dose was calculated for each individual organ in the body and dose volume histograms were computed to analyze the absolute and relative doses in each organ. Results: The neutron irradiations of the liver showed the highest organ dose absorption in the liver, with appreciably lower doses in other proximal organs. The dose distribution within the irradiated slice exhibited substantial attenuation with increasing depth along the beam path, attenuating to ∼15% of the maximum value at the beam exit side. The gamma irradiation of the liver imparted the highest organ dose to the stomach wall. The dose distribution from the gammas showed a region of dose buildup at the beam entrance, followed by a relatively uniform dose distribution to all of the deep tissue structures, attenuating to ∼75% of the maximum value at the beam exit side. For the breast scans, both the neutron and gamma irradiation registered maximum organ doses in the breasts, with all other organs receiving less than 1% of the breast dose. Effective doses ranged from 0.22 to 0.37 mSv for the neutron scans and 41 to 66 mSv for the gamma scans. Conclusions: Neutron and gamma irradiation of a primary target organ was found to impart the majority of the total dose to the primary target organ (and other large organs) within the beam plane and considerably lower dose to proximal organs outside of the beam. These results also indicate that despite the use of a highly scattering particle such as a neutron, the dose from neutron stimulated emission computed tomography scans is on par with other clinical imaging techniques such as x‐ray computed tomography (x‐ray CT). Given the high nonuniformity in the dose across an organ during the neutron scan, care must be taken when computing average doses from neutron irradiations. The effective doses from neutron scanning were found to be comparable to x‐ray CT. Further technique modifications are needed to reduce the effective dose levels from the gamma scans.